Reflective Writing as a Pedagogical Tool to Foster Critical Awareness among Non-English Department Students in Indonesian EFL Contexts - Rizqiani, Diyah Ayu; Astuti, Missi Tri (Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia, 2025)
Reflective journaling has increasingly been applied as an instructional approach to promote critical awareness in higher education, including in non-language disciplines. This research explores the reflective journals produced by students of the Criminology Department at the Faculty of Social and Political Sciences, Universitas Islam Riau, during the even semester of the academic year 2024/2025. The students’ reflections addressed the issue of noise pollution in their immediate environment. The purpose of this study was to analyze students’ levels of critical awareness based on five indicators: issue comprehension, critical reflection, real-life connection, recognition of multiple perspectives, and clarity of expression. A total of fourteen journals were evaluated using a four-point analytic rubric. The results reveal that six journals (43%) reached the “Excellent” level, seven (50%) were classified as “Very Good,” and one (7%) fell into the “Good” category. These findings indicate that most students demonstrated a solid understanding of the topic and were able to establish meaningful links to real-life situations. Nevertheless, limitations were observed in the depth of critical reflection, consideration of diverse perspectives, and clarity of expression, as several journals exhibited only surface-level discussion. In conclusion, the study confirms the effectiveness of reflective writing in fostering critical thinking and civic awareness among non-English department students, while also underscoring the need for systematic instructional support to encourage deeper multi-perspective analysis and more precise academic writing.